2021
DOI: 10.20944/preprints202104.0165.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rethinking Digital Literacy Competencies of Indonesian Nursing Student in IR 4.0: Philosophical Context<em> </em>

Abstract: Background: Industry revolution 4.0 (IR.4.0) paradigm, nurses were required to have adequate competencies to carry out their professional duties. Digital information should be mastered by the nursing student. Purpose: This study aims to explain digital literacy competencies on nursing students in the era of industrial revolution 4.0 in the Indonesian context. Methode: A literature review was conducted in this study using Rayyan Systematic Reviews Software. Results: There was 14 literature analyzed describing S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have also identified that low levels of digital literacy lead to a lack of staff engagement with information systems. 27 Bad computer skills and poor experience in using digital technology can affect staff attitudes toward digital literacy. 28 Therefore, a low level of digital literacy is an obstacle to the development of hospital information systems and smart hospitals, whereas good digital literacy could increase productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also identified that low levels of digital literacy lead to a lack of staff engagement with information systems. 27 Bad computer skills and poor experience in using digital technology can affect staff attitudes toward digital literacy. 28 Therefore, a low level of digital literacy is an obstacle to the development of hospital information systems and smart hospitals, whereas good digital literacy could increase productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reviewed studies, some studies have conducted a review of the literature to understand the status of the adoption of IoT. For instance, [22] reviewed 14 articles pertaining to the adoption of IoT in education. The findings showed that digital literacy is critical for students to enhance their knowledge, skill, and performance.…”
Section: Other Theories and Approachmentioning
confidence: 99%
“…technology acceptance model (TAM) is one of the widely used adoption theory in IoT context [20], [21]. Further, prior review studies are limited in term of the number of articles i.e., 14 articles in [22] or in term of coverage between 1999-2017 in the study of [23], 2008-2020 in the study of [24] or the focus on the learning style and outcome using IoT such as in the study of [25]. Therefore, to understand the findings of prior literature and to draw a direction for future work, this study aims to review the literature and provides the audiences with recommendations to further their understanding regarding the factors that can contribute to the adoption of IoT.…”
Section: Introductionmentioning
confidence: 99%